NEGOTIATING POLITICIANS' RESPONSIBILITIES IN NEWS INTERVIEWS. (16th November 2016) - Ekström, Mats; Djerf-Pierre, Monika; Johansson, Bengt; Håkansson, Nicklas
Abstract : News interviews are contexts in which political responsibilities are articulated and negotiated. Although the accountability interview is recognized as a commonsense practice in journalism, and the research on political interviews is substantial, it partly remains to explore how responsibilities are negotiated in different forms of questioning in journalism. This study investigates three generic forms of questioning: accountability questioning, the clarifying of promises, and the principal assessments. Key features of the different forms are specified. The empirical study investigates how the questionings are performed in news on industrial crises in Sweden, in the different political regimes in the 1970s and the 2000s. The data consist of 27 news interviews with the formally responsible Ministers. The method is based on Conversation Analysis and includes detailed analyses of questions and answers. The study shows (1) how the forms of questioning differ when it comes to the action agenda and in how responsibilities are invoked and negotiated; (2) how the questionings tend to reproduce particular expectations of Governmental interventions; (3) how increased assertiveness and adversarialness in interviewing coincide with reduced expectations of political responsibilities.